A Microstructural Analysis of 2D Halide Perovskites: Stability and Functionality - Bhattacharya, Susmita; Chandra, Goutam Kumar; Predeep, P. (Frontiers in Nanotechnology, 2021)
Recent observations have demonstrated that the photoelectric conversion properties of perovskite materials are intimately related to the presence of superlattice structures and other unusual nanoscale features in them. The low-dimensional or mixed-dimensional halide perovskite families are found to be more efficient materials for device application than three-dimensional halide perovskites. The emergence of perovskite solar cells has revolutionized the solar cell industry because of their flexible architecture and rapidly increased efficiency. Tuning the dielectric constant and charge separation are the main objectives in designing a photovoltaic device that can be explored using the two-dimensional perovskite family. Thus, revisiting the fundamental properties of perovskite crystals could reveal further possibilities for recognizing these improvements toward device functionality. In this context, this review discusses the material properties of two-dimensional halide perovskites and related optoelectronic devices, aiming particularly for solar cell applications.